Solutions of Some Difference Equations Systems and Periodicity - Elsayed, Elsayed M.; Alzahrani, Faris; Abbas, Ibrahim; Alotaibi, N. H. (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this article, analysis and investigation have been conducted on the periodic nature as well as the type of the solutions of the subsequent schemes of rational difference equations with a nonzero real numbers initial conditions.